Strategi Komunikasi Pemasaran Whiz Prime Hotel Surabaya Dalam Upaya Meningkatkan Okupansi - Sasha Meydi Cerilda; Rini Ganefwati; Muhammad Fadeli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
This research describes the marketing communication strategy of Whiz Prime Hotel Surabaya in an effort to increase occupancy amidst tight competition in the hotel business. By using a marketing mix or marketing mix which consists of 4Ps, namely product, price, place, promotion. The aim of this research is to explore the marketing communication strategy carried out by Whiz Prime Hotel Surabaya in an effort to increase occupancy. And to find out what plans are used to carry out marketing communications strategies. This research uses a qualitative descriptive method by conducting observation and interview techniques. The results of this research prove that several efforts made by Whiz Prime Hotel Surabaya in implementing marketing communication strategies are good enough to increase occupancy.